PROGRAM “SITOGA” (SING, STORY, AND GAMES): PELATIHAN BAHASA INGGRIS BAGI GURU TK DESA SENAUNG KABUPATEN MUARO JAMBI - Yahfenel Evi Fussalam; Sylvia Wenny J; Prima Audia Daniel (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2022)
The purpose of this Community Service (PKM) activity is an effort to help teachers of the Jauharul Iman Kindergarten Senaung Village, Jambi Outer City District, Muaro Jambi Regency, Jambi Province, to find, create and apply English learning materials according to the age of the children. To achieve this goal, the PKM activity carried out is SITOGA (Sing, Story and Games) for kindergarten teachers. This activity takes place during the month of April to May 2022, where the first month is focused on deepening material on the principles of teaching English for Young Learners, introducing learning resources, and learning methods and techniques. The next second month becomes an opportunity for participants (kindergarten teachers) in making learning resources and implementing or practicing learning. The results of PKM activities include participants being able to understand theories of teaching English in kindergarten, teachers being able to recognize several English songs, combining songs and movements in English, making simple English teaching media, designing learning activities with fun activities, and getting to know and practice different types of games